Green Accounting as a Sustainability Mechanism Moderating Financial Statement Fraud in the Fraud Pentagon Context: A Study from Indonesia - Permatasari, Maulina; Yulianti, Vista (Journal of Applied Accounting and Taxation, 2025)
Financial statement fraud remains a major threat to corporate transparency and sustainable business practices. Traditional frameworks, such as the Fraud Triangle and Fraud Pentagon, focus on psychological and organizational factors behind fraudulent behavior. However, they often overlook the influence of environmental accountability on corporate ethics. This study examines the effects of pressure, opportunity, rationalization, capability, arrogance, and collusion on financial statement fraud. Green accounting is introduced as a moderating factor linking fraudulent behavior and corporate sustainability. The study uses a quantitative approach, drawing on data from manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2024. Data were collected through financial report analysis and questionnaires. Analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both measurement and structural models. Descriptive statistics, validity, and reliability tests were performed before path analysis. The findings show that the six Fraud Pentagon elements significantly influence the risk of financial statement fraud, though their effects differ in magnitude. Green accounting moderates these relationships by reducing fraudulent tendencies through the integration of sustainability principles in financial reporting. Firms with strong environmental accounting practices show higher transparency and accountability toward both financial and ecological stakeholders. This study concludes that embedding green accounting in corporate governance enhances financial integrity and promotes sustainable business conduct. By extending the Fraud Pentagon through a sustainability lens, the research contributes to fraud theory and corporate environmental responsibility. This has practical implications for regulators, auditors, and managers, who should strengthen the adoption of green accounting as a strategic measure to counter fraudulent financial reporting.